Implementasi Program Public Speaking Skill Pada Kegiatan Ekstrakurikuler Pendidikan Agama Islam - Arizka, Pilma Sindy; Arlina, Arlina (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study is to find out how the implementation of the public speaking skill program activities in PAI extracurricular activities at SMAS An-Nizam Medan, what are the supporting and inhibiting factors and what are the paths after implementing PAI extracurriculars, namely public speaking skills/Kultum at SMAS An-Nizam Medan. This type of research is descriptive qualitative. This research was taken at SMAS An-Nizam Medan. Data collection methods used are observation, interviews, and documentation. The results of the study showed that the PAI extracurricular activities that were implemented were one of the public speaking skills/Kultum programs which were carried out every day after the midday prayer. As for the supporting factors in the implementation of public speaking skills/Kultum, there are professional teachers who are very supportive in motivating students. While the inhibiting factor in this implementation is the lack of self-confidence of introverted students which results in being nervous when in front. Furthermore, the impact of the implementation of the public speaking skill/Kultum program on PAI extracurricular activities is that you can get used to speaking in public, especially later in the community and this program is not obtained in class lessons but only in PAI extracurriculars and can represent the school when there is a speech contest both held by internal and external parties, as well as from government and private sectors.